IMPLEMENTASI KAIDAH ḤAML AL-MUTLAQ `ALᾹ AL-MUQAYYAD DALAM KITAB TAFSIR AL-MUNĬR DAN KITAB TAFSIR AL-JĀMI` LI AḤKĀM AL-QUR’AN - Ikmal, Ikmal; Agil, Mujahid; wahyudi, Wahyudi (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
His study aims to reveal the use of one of the rules of interpretation, namely the rule of ḥaml al-muṭlaq `alā al-muqayyad in the book of interpretation. In this study, the author describes three important points, namely the understanding of muṭlaq and muqayyad, the law in the rule of ḥaml al-muṭlaq `alā al-muqayyad, and the implementation of the rule of ḥaml al-muṭlaq `alā al-muqayyad in two books of interpretation, the interpretation of al-munĭr and the interpretation of al-jāmi` li aḥkām al-qur'an. This type of research is classified as library research with a descriptive comparative analytical method. Through this study, the author explains that muṭlaq is a word that indicates an unlimited entity, while muqayyad is a word that indicates a limited entity. From a legal aspect, muṭlaq and muqayyad have four laws taking into account legal conditions and causes. Wahbah al-zuḥailĭ and al-qurṭubĭ implement the concept of the kiadah ḥaml al-muṭlaq `ala al-muqaayad in their interpretations either explained explicitly or simply explaining universal legal conclusions